Sensory Characteristics of Commercial Lactose-free Milks Manufactured in the United States - Adhikari, Koushik; Dooley, Lauren; Chambers, Edgar, IV; Bhumiratana, Natnicha (My University, 2010)
This study determined the sensory characteristics of ultrapasteurized (UP) lactose-free milk of different fat contents, and compared them with regular milk. Nine milk samples (six UP lactose-free and three regular) containing 0, 2 or 3 g milkfat/100 mL were tested by a descriptive panel. A consumer test with three UP lactose-free milk and three regular samples was also conducted. The skim milks were found to be lacking in freshness and the dairy notes were lower compared to the higher-fat-content milks. The UP lactose-free milks were different from the regular milk because of higher intensities of cooked, processed, and sweet attributes. UP lactose-free milks tended to score higher than the regular milks at the same fat content for dairy-related attributes, but this difference was not significant for the reduced-fat milks. Although majority of the consumers in the present study were aware that UP lactose-free milks existed in the market, only few had tasted them before. The h igher intensities of cooked and sweet flavor attributes in the UP lactose-free milks might be a hindrance to their consumption by the lactose-intolerant population. More efforts are needed from the dairy industry to develop better lactose-free products and to educate consumers about lactose-free dairy products.
Keywords: Ultrapasteurized lactose-free milk; Descriptive analysis; Consumer acceptability; PLS regression